Spirituality and Concept of 'Child' in Kokas Pedagogy for Children with Special Educational Needs - Csilla Imola Székely (Debrecen University Press, 2020)
Klára Kokas was a music teacher and music psychologist (1929-2010). Her method is based on music, motion and manual arts, therefore it can be defined as a form of reform pedagogy, otherwise it is called complex art pedagogy. The main elements and characteristics of Klára Kokas's pedagogy were revolutionary new ideas in the fields of personality development, and music education - compared to the practices of reform pedagogy trends in the 20th century Europe and the United States (Pukánszky-Németh, 1996). The main elements of this concept are music, dance improvisation, motion, imaginative stories, visual arts, painting and drawing. However, its most important component is the very specific and intimate relation, which connected her to children. This distinctive feature of the Kokas-method is hard to teach. Klára Kokas approached to people with problems, suffering and disabilities, especially to marginalized and disadvantaged children with utmost empathy. She struggled to develop the social-cognition skills and affectionate behavior of the handicapped children through her own invented musical method.Her writings reflected her relationship with God, namely the presence of Him which can be felt behind the scenes. His name was mostly unspoken, yet when she named Him, it was to reveal that God was always in her mind, like in her words and musical activities too.The goal of this paper is to search and frame that text corpus, which can outline the spirituality of Klára Kokas with the aim of drawing up her relationship with God and children - according to her publications, writings, essays, books, short-film compilations, movie archives and interviews (Kokas, 1992; 1999; 2002; 2007; 2012; 2013). The contours of her spirituality from her teachings, manuscripts and publications couldn't be attributed to any religious denomination. Also, to be presented are her notions about youth and teenage spirit and a unique relation with the world, her own students, the talents, the music and the holiness: the spirituality of Klára Kokas. The importance of beliefs and moral convictions in the art of education will be outlined.A single paragraph of about 150-200 words maximum. For research articles, abstracts should give a complete overview of the work. We encourage authors to use the following style of abstracts: background, methods, results and conclusion. The abstract should give an objective representation of the article.